Intracranial infections related to external ventricular drains in neurocritical care patients : diagnosis and treatment implications - Marcus Ståhlberg (2025)
This thesis addresses the critical challenge of diagnosing and managing external ventricular drain-associated infections (EVDIs) in neurocritical care. The neurosurgical intensive care unit (NICU) frequently admits patients with severe brain injuries, often requiring neurosurgical interventions such as external ventricular drain (EVD) placement to manage increased intracranial pressure (ICP) caused by intracranial hemorrhage and intraventricular hemorrhage. Although EVDs are essential for cerebrospinal fluid (CSF) diversion and ICP monitoring, they carry substantial risks, notably bacterial infections, which pose diagnostic and therapeutic dilemmas due to ambiguous clinical signs and the limitations of current EVDI surveillance methods. The resulting overuse of broad-spectrum antibiotics exacerbates concerns about antimicrobial resistance and patient safety. The overarching aim of this thesis was to critically appraise existing EVDI surveillance practices and develop improved or adjunct diagnostic strategies and methods to potentially guide EVDI-targeted treatment.In Study I we investigated the assumption that blood is evenly distributed within the ventricular space, an assumption underpinning current cell count-based infection markers. Using paired CSF samples before and after patient repositioning in the ICU, significant bi-directional variability in cell counts, glucose, and lactate was observed, affecting the EVDI classification of 30% of all patients. These findings challenge the validity of cell count metrics in EVDI surveillance, introducing considerable uncertainty in their use to inform clinical decision-making.In Study II we retrospectively assessed the performance of routine EVDI surveillance diagnostics at Karolinska University Hospital over a 17-year period. Results demonstrated poor discriminatory power of current EVDI surveillance diagnostics between infection and aseptic inflammation, contributing to a seven-to-one ratio of suspected to verified infections. Moreover, 15% of all ICU antibiotic use could be attributed to EVDI-targeted therapy, despite EVDI patients only representing approximately 3% of the total ICU population at our institution. Overall our findings suggested a need for more specific and sensitive methods to guide EVDI-targeted therapy.In Study III we retrospectively evaluated the potential use of 16S-rRNA sequencing, a molecular diagnostic technique capable of detecting bacterial genetic material, compared to the current gold standard CSF cultures in EVDI diagnostics. The study demonstrated comparable sensitivity and specificity, albeit lower positive predictive value, with the potential to reduce broad-spectrum antibiotic usage by 43-71% if results are obtained within 24 hours. As such, representing a promising method for potentially guiding EVDI-targeted therapy and improving antimicrobial stewardship.In Study IV, a proof-of-concept study, we prospectively evaluated a novel diagnostic platform based on loop-mediated isothermal amplification (LAMP) technology. EVDI specific test kits, tailored to detect EVDI-relevant bacterial pathogens, were developed through the compilation of microbiological findings globally through an extensive literature review as well as through the compilation of microbiological findings at our institution over a 15-year period. Our findings in this study suggests that LAMP- based methods, while demonstrating a high rate of contaminations, can facilitate timely pathogen identification, enabling targeted therapy and reducing unnecessary antibiotic exposure in an ICU setting.Overall, this research underscores the limitations of current EVDI surveillance paradigms and highlights promising current and future rapid molecular diagnostic testing modalities as tools for more accurate, sensitive, and timely infection detection. Implementing such adjunct diagnostics can potentially reduce broad-spectrum antibiotic use, mitigate antimicrobial resistance, and improve clinical outcomes in neurocritical care patients. Future efforts should focus on further exploring and integrating these innovative strategies into routine practice and evaluating their impact in prospective clinical trials.List of scientific papersI. Cerebrospinal fluid cell count variability is a major confounding factor in external ventricular drain-associated infection surveillance diagnostics: a prospective observational study. Marcus Bådholm, Jonas Blixt, Martin Glimåker, Anders Ternhag, Jonas Hedlund, and David W. Nelson Critical Care 25, no. 291 (11 August 2021). https://doi.org/10.1186/s13054-021-03715-1II. Performance of routine surveillance diagnostics of external ventricular drain- associated infections in a critical care setting: a retrospective cohort study. Marcus Ståhlberg, Jonas Blixt, Christer Mehle, Viveca Hambäck Hellkvist, Christian G. Giske, Eddie Weitzberg, and David W. Nelson Infectious Diseases 25, no. 646 (02 May 2025). https://doi.org/10.1186/s12879-025-11006-1III. Next-generation 16S-rRNA sequencing for diagnosing external ventricular drain-related infections in a critical care setting: a multi-center cohort study with implications for antibiotic stewardship. Marcus Ståhlberg, Joel Rahme, John Karlsson Valik, Christer Mehle, Jonas Blixt, Eddie Weitzberg, Christian G. Giske, and David W. Nelson. [Manuscript]IV. Loop-mediated isothermal amplification as a novel approach for early identification of meningitis in patients with external ventricular drains in a critical care setting: a prospective clinical proof-of-concept study. Marcus Ståhlberg, John Karlsson Valik, Jonas Blixt, Stina Hardell, Anette Ebberyd, Viveca Hambäck Hellkvist, Eddie Weitzberg, Christian G. Giske, and David W. Nelson. [Manuscript]